2021
DOI: 10.3390/cryst11050530
|View full text |Cite
|
Sign up to set email alerts
|

CHCl3-Dependent Emission Color and Jumping Behavior of Cyclic Chalcone Single Crystals: The Halogen Bond Network Effect

Abstract: As a conventional strategy to modulate the structure and properties of inorganic single crystals, hydration/solvation is rarely found to function in pure organic single crystal. Herein, we report chalcone single crystals with CHCl3-dependent emission color and jumping behavior. Two crystals: a pure crystal phase (1) with green-yellow emission and a CHCl3-containing co-crystal phase (1•2CHCl3) with orange-red emission were constructed by fine-controlling the crystallization conditions. The special halogen bond … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
4
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 30 publications
0
4
0
Order By: Relevance
“…19b). 109 A pure crystalline phase (1) with greenish-yellow emission and a CHCl 3 -containing eutectic phase (1–2CHCl 3 ) with orange-red emission were designed by incorporating the D–A units. Notably, the [2+2] photocycloaddition reaction of the pure crystalline phase ( 1 ) exhibited a strong light-induced jumping behaviour due to the molecular stacking effect.…”
Section: Photoresponsive Fluorescent Materials Based On [2+2] Photocy...mentioning
confidence: 99%
“…19b). 109 A pure crystalline phase (1) with greenish-yellow emission and a CHCl 3 -containing eutectic phase (1–2CHCl 3 ) with orange-red emission were designed by incorporating the D–A units. Notably, the [2+2] photocycloaddition reaction of the pure crystalline phase ( 1 ) exhibited a strong light-induced jumping behaviour due to the molecular stacking effect.…”
Section: Photoresponsive Fluorescent Materials Based On [2+2] Photocy...mentioning
confidence: 99%
“…4e). 97 In this crystal, chlorine atoms may interact with the lone pair electrons of nitrogen in the triphenylamine moiety (C-ClÁ Á ÁN, 3.993 Å). Meanwhile, the intermolecular hydrogen bonds (C-HÁ Á ÁO, C-HÁ Á ÁCl), halogen bonds (C-ClÁ Á ÁN, 3.993 Å) and p-p interactions are responsible for the similar molecular packing in the crystal of 7 to that of 6, and the distance of the ''olefin pair'' was 3.622 Å.…”
Section: Halogen Effect In Photomechanical Molecular Crystals Fueled ...mentioning
confidence: 99%
“…As can be seen from the crystalline structure, hydrogen bonds involving fluorine atoms are abundant. It was suggested that the contraction along the long axis at the beginning of UV irradiation led to the bending toward the light source and the reaction gradient with a prolonged 97 irradiation time caused the crystal to swing (Fig. 5e).…”
Section: Halogen Effect In Photomechanical Molecular Crystals Fueled ...mentioning
confidence: 99%
See 1 more Smart Citation